2015
DOI: 10.1371/journal.pone.0141641
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cardiovascular Mortality 10 Years after Supplementation with Selenium and Coenzyme Q10 for Four Years: Follow-Up Results of a Prospective Randomized Double-Blind Placebo-Controlled Trial in Elderly Citizens

Abstract: BackgroundSelenium and coenzyme Q10 are important antioxidants in the body. As the intake of selenium is low in Europe, and the endogenous production of coenzyme Q10 decreases as age increases, an intervention trial using selenium and coenzyme Q10 for four years was performed. As previously reported, the intervention was accompanied by reduced cardiovascular mortality. The objective of the present study was to analyze cardiovascular mortality for up to 10 years after intervention, to evaluate if mortality diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 44 publications
4
79
0
7
Order By: Relevance
“…The beneficial effects of CoQ10 supplementation on the diabetes-induced abnormalities and complications in diabetic patients receiving regular medications have been revealed in several clinical trials [80-85]. In addition, combination therapy exerts more beneficial effects in the treatment of diabetes-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of CoQ10 supplementation on the diabetes-induced abnormalities and complications in diabetic patients receiving regular medications have been revealed in several clinical trials [80-85]. In addition, combination therapy exerts more beneficial effects in the treatment of diabetes-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a prospective randomized, double‐blind, placebo‐controlled study evaluated the effects of combined chronic supplementation of Se (200 μg organic Se) and 200 mg coenzyme Q10 per day on the severity of chronic heart failure, all‐cause mortality, and cardiovascular mortality . The intervention was performed for 4 years, and the authors observed that chronic treatment with Se and Q10 resulted in a reduced inflammatory status in these patients and significantly reduced cardiovascular mortality assessed after 10 years …”
Section: The Role Of Se In Cardiac Surgerymentioning
confidence: 99%
“…The administration of low doses of Se at only a few time points will probably have no significant effects on the circulating Se blood levels, bioavailability, or the patient's clinical outcome . In contrast, a more frequent administration of Se might have more pronounced effects on reducing new infections in critically ill patients . Additionally, there is no consensus about whether Se should be administered as a bolus or as a continuous infusion.…”
Section: The Role Of Se In Cardiac Surgerymentioning
confidence: 99%
“…It should be noted that those who had received active intervention and were included in the study had only been treated for the initial 48 months. But as previously reported, a significant cardioprotective effect remained also after 10 years [53]. It is tempting to speculate if a prevention of structural changes induced by the decelerated fibrogenesis explains this long-lasting cardioprotection.…”
Section: Effect Of Intervention With Selenium and Coenzyme Q10 On Biomentioning
confidence: 50%